Impact of Sleep Disorders on Daily Functioning in Children with Autism Spectrum Disorder - Foster, Liam J. (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aims to explore the impact of sleep disorders on daily functioning in children with Autism Spectrum Disorder (ASD) through the perspectives of their caregivers. A qualitative research design was employed, involving semi-structured interviews with 23 caregivers of children aged 4-12 years diagnosed with ASD. Participants were recruited through local autism support groups, special education schools, and pediatric clinics. Interviews focused on the types, frequency, and severity of sleep disorders, their impact on the child's behavior, academic performance, social interactions, physical health, and family dynamics, as well as the strategies used to manage these issues. Thematic analysis was used to identify key themes and patterns from the data. The study identified several types of sleep disorders among children with ASD, including insomnia, sleep apnea, and night terrors, varying in frequency and severity. Sleep disturbances were found to significantly impact daily functioning, leading to behavioral issues, academic challenges, social difficulties, and physical health problems. Caregivers employed a range of coping strategies, such as medical interventions, behavioral routines, environmental modifications, dietary adjustments, and alternative therapies, with varying degrees of success. Barriers to effective management included cost, accessibility, and lack of knowledge. The need for individualized, adaptive approaches to treatment was emphasized. Sleep disorders in children with ASD have profound effects on their daily functioning and overall quality of life. Addressing these issues requires a comprehensive, individualized approach that considers the unique needs of each child. Collaboration with caregivers and regular adjustments to intervention strategies are essential for effective management. Further research should focus on larger, more diverse samples and incorporate objective sleep measures to provide a more comprehensive understanding of these challenges.